"Arab women's Spring" revisited: media attitudes and public opinion in Germany. Issue 2 (17th February 2021) - Mustafa-Awad, Zahra; Kirner-Ludwig, Monika; Sawalha, Majdi
ABSTRACT: This study is part of a project investigating the impact of Arab women's representation in Western news discourse during the Arab Spring on changing their stereotypes in media and on public opinion in Germany. We focus on relating the themes associated with them and reflected in articles published by German, British, and American news media to German university students' attitudes towards them. We adopted discourse analysis and corpus linguistic approaches in examining the effects of lexical choices in the news on changing their recurrent images in media and on their perception in Germany. Our results show that the relevant expressions reflect two sets of themes: one is connected to the uprisings highlighting their rebellion and activism, while the other is linked to their portrayal in Western media as oppressed victims. These themes were indicated in the students' responses in addition to others that are not visible in the news. While our findings confirm a shift in Arab women's established stereotypes in the news as well as in our participants' perception of them, they provide further evidence for the effect of news on public opinion. For our students, this impact is clearly balanced out by their critical reading and thinking skills.